2014
DOI: 10.1016/j.jconrel.2013.12.014
|View full text |Cite
|
Sign up to set email alerts
|

A robust and quantitative method for tracking liposome contents after intravenous administration

Abstract: We introduce a method for tracking the rate and extent of delivery of liposome contents in vivo based on encapsulation of 4-methylumbelliferyl phosphate (MU-P), a profluorophore of 4-methylumbelliferone (MU). MU-P is rapidly dephosphorylated by endogenous phosphatases in vivo to form MU after leakage from the liposome. The change in fluorescence spectra when MU-P is converted to MU allows for quantification of entrapped (MU-P) and released (MU) liposome contents by fluorescence or by a sensitive high performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…This term describes the fraction of drug released from the liposome and available for therapeutic activity [51]. The presence of both MU and MU-P in the tumor 48 hours after administration indicates the persistence of intact liposomes, and the presence of MU supports the hypothesis of sustained MU-P release from liposomes to inhibit HA synthesis (Figure 3D).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…This term describes the fraction of drug released from the liposome and available for therapeutic activity [51]. The presence of both MU and MU-P in the tumor 48 hours after administration indicates the persistence of intact liposomes, and the presence of MU supports the hypothesis of sustained MU-P release from liposomes to inhibit HA synthesis (Figure 3D).…”
Section: Resultsmentioning
confidence: 82%
“…MU-P is rapidly dephosphorylated over the course of minutes to form MU in serum (Figure 1B) and in a number of tissue homogenates [51]. This conversion is slower in heat-inactivated serum, indicating a loss in endemic serum phosphatases (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found that at acyl chain lengths of C 16 and C 18 , SML liposomes are more stable in circulation than liposomes containing free cholesterol. Further, we found that these SML liposomes had improved uptake into and slower clearance from the liver and spleen compared to traditional liposomes [136]. These studies highlight the stability of SML systems in vivo and their potential utility as drug carrier systems.…”
Section: Lipids That Direct Membrane Biophysics and Payload Releasementioning
confidence: 88%
“…SMLs are easily synthesized, commercially available, and recapitulate the biophysical properties of liposomes incorporating cholesterol [134136]. Compared to liposomes formulated with free cholesterol, SMLs eliminate the phase transition of diacylphospholipids [135], exhibit similar permeability to entrapped hydrophilic molecules [135,136] and demonstrate similar membrane fluidity [136]. SMLs maintain these properties while preventing cholesterol transfer from the bilayer [135].…”
Section: Lipids That Direct Membrane Biophysics and Payload Releasementioning
confidence: 99%